The Role of ESG in Moderating Effects on Profitability in the Pharmaceutical Industry - Try Kurnia Putra; Amanah Hijriah; Vitriyan Espa (Golden Ratio of Auditing Research, 2026)
This study aims to examine the effect of exchange rate fluctuations, capital structure, and growth opportunities on profitability, with Environmental, Social, and Governance (ESG) factors as a moderating variable, in officially listed pharmaceutical companies on the Indonesia Stock Exchange (IDX).  The observation period covers 2019 to 2023. The analytical method used is Multiple Linear Regression Analysis, with SPSS version 30 as the data processing tool.  This study finds that within Indonesia’s pharmaceutical industry, capital structure has a significantly negative effect on profitability, while growth opportunities exert a significantly positive influence. Meanwhile, exchange rate fluctuations show no significant effect. Crucially, good ESG management is proven to moderate and reduce the profitability losses arising from high debt levels, but it does not affect other variable relationships. The practical implication is that pharmaceutical companies should minimize debt dependence and optimize ESG investments as a fundamental risk mitigation strategy to safeguard and enhance long-term profitability.